2009
DOI: 10.1073/pnas.0809847106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a C-terminus domain critical for the sensitivity of Kir2.1 to cholesterol

Abstract: A variety of ion channels are regulated by cholesterol, a major lipid component of the plasma membrane whose excess is associated with multiple pathological conditions. However, the mechanism underlying cholesterol sensitivity of ion channels is unknown. We have recently shown that an increase in membrane cholesterol suppresses inwardly rectifying K ؉ (Kir2) channels that are responsible for maintaining membrane potential in a variety of cell types. Here we show that cholesterol sensitivity of Kir2 channels de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 36 publications
9
98
2
Order By: Relevance
“…This suggests that the interactions between the subunits that couple their coordinated motion are important for this process. This observation is consistent with our previous observation that the L222I mutation has a dominant negative effect on cholesterol sensitivity of the channel, 18 and implies that more than one subunit is required for cholesterol to suppress channel activity.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This suggests that the interactions between the subunits that couple their coordinated motion are important for this process. This observation is consistent with our previous observation that the L222I mutation has a dominant negative effect on cholesterol sensitivity of the channel, 18 and implies that more than one subunit is required for cholesterol to suppress channel activity.…”
Section: Discussionsupporting
confidence: 82%
“…18,34 Moreover, these data were in agreement with the effect of cholesterol on native Kir2 channels in aortic endothelial cells 40 and in atrial myocytes. 41 In addition, we have recently shown that cholesterol treatment of Xenopus oocytes expressing several Kir2.1 mutants including L222I reproduces the effect of cholesterol on the corresponding mutants in HEK cells.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…Hypercholesterolemia suppressed the inward rectifying potassium current in endothelial cells (which might be expected to lead to diminished NO response to acute changes in flow) (501). Hypercholesterolemia seems to directly affect PIP 2 sensing amino acids in inwardly rectifying K (Kir2) channels (482). Interestingly, patients with familial hypercholesterolemia were shown to have reduced glycocalyx volume which could be partially restored by treatment with rosuvastatin (1202).…”
Section: Hyperlipidemiamentioning
confidence: 99%